Generating arguments based on Data-oriented Belief Revision model - Morveli-Espinoza, Mariela; Tacla, Cesar A. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2014)
Data-Oriented Belief Revision (DBR) is a relatively recent approach that claims the difference between pieces of information gathered and stored by agent (data) and information revised and considered reliable (beliefs). Data structure proposed in DBR can also be used to implement the structure of an argument. It’s worth noting that this approach can be considered as the first step to integrate both belief revision and argumentation areas and allowing them to be modeled in the same framework. Our objective is to continue making progress on this research from a computational view. This article is our first step, here we propose two ways to generate arguments and counter-arguments in a monological argumentation based on the DBR model’s data structure.